Seeing, Saving, and Remembering Barnardo’s Children: Technologies of Access and Preservation in Historical Research - Vestberg, Nina (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2022)
This essay explores how photography and digitization have shaped access to and preservation of key sources of the historical phenomenon of child migration from the UK to Canada, as organized by Barnardo’s charity. It examines two case studies illustrating how stakeholders in the history of Barnardo’s have adopted digital technologies and networks to ensure the continued preservation and dissemination of photographic sources of that history. Focusing on the significance of digital tools in the process of researching case studies, this discussion opens up broader questions of the role of access and preservation technologies in transnational historical research.